Methodology for quantifying engineered nanomaterial release from diverse product matrices under outdoor weathering conditions and implications for life cycle assessment. Issue 9 (11th August 2017) - Lankone, Ronald S.; Challis, Katie E.; Bi, Yuqiang; Hanigan, David; Reed, Robert B.; Zaikova, Tatiana; Hutchison, James E.; Westerhoff, Paul; Ranville, James; Fairbrother, Howard; Gilbertson, Leanne M.
Abstract : Accurate measurement of engineered nanomaterial (ENM) release from diverse product lines and matrices during use is critical to evaluating environmental impacts across the life cycle of a nano-enabled product. Abstract : Accurate measurement of engineered nanomaterial (ENM) release from diverse product lines and matrices during use is critical to evaluating environmental impacts across the life cycle of a nano-enabled product. While indoor accelerated weathering and a handful of outdoor weathering case studies exist, there has not been a standard methodology applied to characterize ENM release during outdoor weathering suitable for simultaneous use in multiple geographic locations. Such an approach has been established and is presented herein, to quantify ENM release and product transformations with the additional goal of improving life cycle assessments (LCA) of nano-enabled products. A team of experimentalists and life cycle practitioners engaged in the development of the methodology to ensure the data collected is useful to inform improved LCA and environmental impact characterization. While the method was developed to be broadly applicable, the examples included here are representative polymer nanocomposite (PNC) platforms, including multiple ENMs ( i.e., nano-silver and carbon nanotubes) within different polymer matrices ( i.e., polystyrene, poly(methyl methacrylate), and polycaprolactone). This unique methodology enables the study of ENM release under real climate conditions ( i.e., composites are weathered outside) that coordinates: (i) multiple locations with distinct climates, (ii) the application of appropriate techniques to quantify ENM release at low (μg) released masses, (iii) tracking changes in efficacy as a function of weathering, and (iv) acquiring data to inform life cycle assessment. Initial findings (following one year of weathering polymer matrices) are included to demonstrate the type of data acquired and utility of the analysis enabled by this method.